Copper(ii)-catalyzed methoxylation of unactivated (hetero)aryl C–H bonds using a removable bidentate auxiliary1. Issue 2 (23rd February 2015) - Yin, Xue-Song; Li, Yi-Chen; Yuan, Jun; Gu, Wen-Jia; Shi, Bing-Feng
<x xml:space="preserve">Abstract</x> A copper-catalyzed methoxylation of unactivated (hetero)aryl C–H bonds has been developed.